Evaluation of peritoneal reinfection after fecal peritonitis - Alberti,Luiz Ronaldo (2012)
PURPOSE: To investigate the role of a previous abdominal infection on peritonitis. METHODS: Twenty-seven adult female Wistar rats were submitted to fecal peritonitis by an intraperitoneal injection of a solution of rat feces. The animals were divided into three groups (n = 9 each): Group 1 - control - intraperitoneal injection of an amount of fecal solution known to be lethal (10 ml/kg), Group 2 - reinfection - intraperitoneal injection of an amount of fecal solution known not to be lethal (2 ml/kg) followed by an injection of fecal solution (10 ml/kg) 30 days later, Group 3 - late reinfection - intraperitoneal injection of 2 ml/kg feces followed by an injection of 10 ml/kg four months later. RESULTS: All animals in Group 1 died within seven days after injection of the fecal solution. In contrast, in the pre-infected Group 2 only one animal died 24 hours after injection of the fecal solution (10 ml/kg). In Group 3, eight of the nine animals in each subgroup died over a period of seven days. The difference in survival time between groups 1, 2 and 3 was for p = 0.0042 (logrank test). CONCLUSIONS: Milder peritoneal sepsis due to fecal infection raises the organic resistance to a new more intense fecal contamination occuring after a short period of time. However, this protection did not persist over a prolonged period of time.